Equilibrium Analysis of Vertical Mergers. (September 2020) - Das Varma, Gopal; De Stefano, Martino
Vertical mergers are known to potentially create an incentive for the merged firm to raise the price of inputs it supplies to its rivals (raising rivals' cost [RRC]). At the same time, vertical mergers are known to create efficiencies in the form of elimination of double marginalization (EDM). Competitive effects of vertical mergers are evaluated as the net effect of RRC and EDM. Conventional antitrust techniques treat the two effects—RRC and EDM—as separable and analyze each in isolation before evaluating their net effect. We show that in an equilibrium treatment, RRC and EDM are not separable; instead, they are inseparably linked because the size of EDM is an important determinant of the strength of the RRC incentive. When the link between EDM and RRC is taken into account, predicted price effects of a vertical merger can turn out to be significantly different relative to those predicted by conventional techniques. Under certain commonly used assumptions, a vertical merger may even create an incentive for the merged firm to lower its rivals' cost. The precise price effect depends on two things: the shape of demand and the bargaining power of the upstream input supplier in its price negotiations with downstream firms.